KEPEMIMPINAN SITUASIONAL DALAM MENINGKATKAN KINERJA GURU DI ERA REVOLUSI INDUSTRU 4.0 - Tresna Permata Agustiani, Tresna Permata Agustiani; Deni Rahman, Deni Rahman; Heris ZA, Heris ZA; Giri Waluyo, Giri Waluyo; Hanafiah, Hanafiah (Wali Pikir: Journal Of Education, 2024)
This research article was written with the aim of knowing and studying the situational leadership of the Principal as an effort to encourage increased learning competence in Educators in the era of the industrial revolution 4.0. This article uses a literature study method or library study where the data sources are obtained from various sources of articles and literature books that are relevant to the topic of the article discussion. The results of writing teacher articles are expected to have effective learning abilities or competencies in the era of the Industrial Revolution 4.0. The Principal can carry out several strategies in improving teacher learning competencies, including by conducting teacher development programs through education and training, strengthening teacher abilities in the use of virtual reality-based learning media through focus group discussion (FDG) activities, developing electronic-based learning modules (E-Modules), developing learning competencies by honing teachers’ digital literacy skills.